Analisis Faktor Project Based Learning Melalui Grand Teori S-O-R pada Manajemen Pemasaran - Suryadi; Joko Samboro; Dika Rizky Yunianto (Unit Pelaksana Teknis Penelitian dan Pengabdian kepada Masyarakat (UPT P2M) Politeknik Negeri Malang, 2023)
Changes in the Independent Curriculum Free Learning in the Industrial Revolution Era 4.0 is a challenge for changing the learning paradigm, communicating the affective domain in the Gradation of Attitudes, Knowledge and skills that require the concept of Stimulus Organism Response. Implementation of this learning is a continuation of Blended in type discovery and problem base learning (Suryadi, et al 2020) which shows a very effective impact for project tasks according to industry needs. Project based learning is a scientific learning model that emphasizes students to learn to find and discover for themselves an incomplete concept or principle. The research objective is to analyze the dominant factors of the Marketing Management project base learning model. This research method is